THE EFFECT ON PRODUCT QUALITY AND PRICE ON CONSUMER PURCHASING DECISIONS OF MIE GACOAN JABABEKA - Permata Jati, Lintang; Ajat Sudrajat (Strategic Management Business Journal, 2024)
Mie Gacoan, a rapidly growing fast-food chain in Indonesia, established in 2016 by PT Pesta Pora Abadi, is known for its signature spicy noodles. With over 100 branches by 2024, including two in Cikarang City, the restaurant is popular for its affordable, high-quality, spicy noodle dishes. This quantitative research explores the impact of product quality and price on consumer purchasing decisions at Mie Gacoan Jababeka, analyzing responses from a population of 1,000 consumers aged 16 and above. Validity, reliability, normality, multicollinearity, heteroscedasticity, F test, multiple linear regression, and T tests were conducted. The t-test results reveal that both product quality and price significantly influence purchasing decisions, aligning with some previous studies but contradicting others. Product quality explains a substantial part of the purchase decision, confirming hypothesis H1, while price also plays a significant role, supporting hypothesis H2. These factors collectively explain 61% of the variation in purchasing decisions, with the remaining 39% attributable to other variables not encompassed within the scope of this study. JEL Classification: M31, D12, L66